EFFET DE LA TOXICITE MANGANIFERE SUR LES PARAMETRES MORPHOMETRIQUES DE LA ROSELLE (HIBISCUS SABDARIFFA L.VAR.SABDARIFFA) AU GABON - Ontod, Tshi-Tshi D.S.; Lepengue, A.N.; M’batchi, B. (European Scientific Journal, ESJ, 2013)
﻿Manganese is one of Gabon main sources of foreign currency. However, its opencast mining poses the problem of environmental pollution in the extraction area. The present work was undertaken to study the effect of manganese on roselle’s (Hibiscus sabdariffa L. var. sabdariffa) growth in greenhouse conditions. Roselle seeds were sowed and grown on three enriched manganese soils (25% Mn, 50% Mn and 75% Mn). The effect of manganese on cultivated roselle was measured by looking at plant morphometric indices and comparing them with reference samples. Result showed that manganese induces leave chlorosis and reduces roselle growth parameters: longitudinal and diametric growth, leave area, fresh and dry matters. These decreases are proportional to manganese concentration. The lowest concentration (25% Mn) produces slight decrease or stimulate roselle morphometric growth parameters